2022
DOI: 10.1002/aenm.202201713
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reconstruction of Water Splitting Electrocatalysts

Abstract: Gibbs free energy (ΔG) of water splitting reaction is 237.2 kJ mol −1 , corresponding to a theoretical voltage of 1.23 V. [3] However, the existence of electrochemical/concentration polarization and solution resistance can increase the actual voltage of water electrolysis to much beyond 1.23 V. Particularly, the OER involves a complicated four-electron transfer process, which results in a sluggish kinetics thus has long been the bottleneck. [4] Therefore, it is necessary to explore efficient and robust electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(82 citation statements)
references
References 185 publications
0
77
0
Order By: Relevance
“…The conjugation of different reconstruction strategies, such as surface activation, heterostructure construction, defect engineering, ionic doping, partial dissolution, and deep reconstruction, may lead to a more active catalytic surface. [ 24 , 25 ] On the other hand, excessive reconstruction may destroy the structural stability of the catalysts due to the serious dissolution of components, resulting in the loss of catalysts’ stability. [ 26 ] Therefore, the depth of reconstruction should be tuned to inhibit the dissolution of active species and eventually obtain an OER catalytic interface with efficiency and stability.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugation of different reconstruction strategies, such as surface activation, heterostructure construction, defect engineering, ionic doping, partial dissolution, and deep reconstruction, may lead to a more active catalytic surface. [ 24 , 25 ] On the other hand, excessive reconstruction may destroy the structural stability of the catalysts due to the serious dissolution of components, resulting in the loss of catalysts’ stability. [ 26 ] Therefore, the depth of reconstruction should be tuned to inhibit the dissolution of active species and eventually obtain an OER catalytic interface with efficiency and stability.…”
Section: Introductionmentioning
confidence: 99%
“…The two important unresolved questions for TMCs as OER electrocatalysts are how the surface reconstructs during the OER and how the TMCs affect the activity/stability of the actual active sites. 163 Although there is no consensus on these open questions yet, many works in recent literature attempted to unveil the underpinning mechanism from different case studies. 164 For example, chalcogenides transformed from LDHs are recently reported showing high performance of OER 165,166 Xu et al 15 reported an iron-doped TMDs (Ni x Fe 1−x Se 2 ) derived from corresponding LDHs with edge active sites for OER.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…The two important unresolved questions for TMCs as OER electrocatalysts are how the surface reconstructs during the OER and how the TMCs affect the activity/stability of the actual active sites . Although there is no consensus on these open questions yet, many works in recent literature attempted to unveil the underpinning mechanism from different case studies .…”
Section: The Surface Reconstruction Of Transition Metal Chalcogenides...mentioning
confidence: 99%
“…[25][26][27][28][29][30][31] This in situ reconstruction process could adjust the electrocatalytic behaviors and thus improve the catalytic performance. 32 For instance, Dai and co-workers reported an outstanding hierarchical anode catalyst consisting of a nickel-iron hydroxide layer coated on a nickel sulde layer that affords superior catalytic activity and corrosion resistance in alkaline seawater electrolysis. 33 Note that the in situ generated polyanion-rich passivating layers are responsible for high corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%